Body composition of the upper limb associated with hypertension, hypercholesterolemia, and diabetes - Qi, Qianjin; Sun, Kui; Rong, Ying; Li, Zhaoping; Wu, Yixia; Zhang, Di; Song, Shuaihua; Wang, Haoran; Feng, Li (Frontiers in Endocrinology, 2022)
The associations between segmental body composition and metabolic diseases remain equivocal. This study aimed to investigate this association using the example of U.S. adults. This cross-sectional study included 12,148 participants from the National Health and Nutrition Examination Survey (NHANES) (2011-2018). Multivariable logistic regression models were used to estimate associations between segmental body composition quartiles of hypertension, hypercholesterolemia, and diabetes. Among 12,148 participants, 3,569, 5,683, and 1,212 had hypertension, hypercholesterolemia, and diabetes, respectively. After adjusting for potential confounders, increased percent upper limb lean body mass was associated with a lower risk of hypertension (OR= 0.88, 95%CI: 0.84, 0.92, P trend<0.001), hypercholesterolemia (OR= 0.93, 95%CI: 0.89, 0.96, P trend<0.001), and diabetes (OR= 0.96, 95%CI: 0.95, 0.98, P trend<0.001). Increased upper limb fat mass is associated with an increased risk of hypertension (OR= 1.11, 95%CI: 1.07, 1.15, P trend<0.001), hypercholesterolemia (OR= 1.05, 95%CI: 1.01, 1.09, P trend=0.07), and diabetes (OR= 1.03, 95%CI: 1.01, 1.05, P trend=0.014). The same correlations were found in the torso and whole-body composition parameters. We observed that for women, lean body mass has a better protective effect on metabolic diseases [hypertension (OR= 0.88, 95%CI: 0.82, 0.93), hypercholesteremia (OR =0.86, 95%CI: 0.81, 0.92), diabetes (OR= 0.97, 95%CI: 0.85, 0.99)]; for men, increased body fat is associated with greater risk of metabolic disease[hypertension (OR= 1.24, 95%CI: 1.15, 1.33), hypercholesteremia (OR =1.09, 95%CI: 1.01, 1.18), diabetes (OR= 1.06, 95%CI: 1.01, 1.10)]. There were significant differences between different gender. These findings suggested that upper limb and torso adiposity should be considered when assessing chronic metabolic disease risk using body composition.